Nearly catastrophe coronary perforation: Is it second drug-eluting stent effective? - Munirwan, Haris; Hadi, Tjut F.; Purnawarman, Adi; Latief, Muhammad H.; Wattanasiriporn, Wittawat; Yusrizal, Teuku (Narra J, 2024)
Coronary artery perforation (CAP) is an uncommon yet serious complication. Although severe perforations (Ellis III) have become more frequent, the overall mortality rate associated with perforations (7.5%) has decreased in recent years. Unfortunately, our medical facility cannot always access a cover stent. The aim of this case report was to demonstrate the effectiveness of using a second drug-eluting stent as an alternative and successful treatment approach in a CAP patient. This is the case of a 67-year-old female with stable angina pectoris Canadian Cardiovascular Society classification III (CCS III), three-vessel coronary artery disease (CAD), who declined CABG (Syntax score of 44) and had type II diabetes mellitus. The patient underwent elective percutaneous coronary intervention (PCI), and we identified diffuse stenosis in the proximal to distal portions of the left anterior descending artery (LAD) with extensive calcification. Furthermore, there was a chronic total occlusion (CTO) in obtuse marginal (OM) 2, as well as critical stenosis in OM3, 80% stenosis in the proximal part of right coronary artery (RCA), 90% stenosis in the middle of the RCA, 90–95% in the distal RCA, and diffuse stenosis ranging from 70–80% in the distal posterolateral. During the procedure to alleviate the stenosis in the left circumflex artery (LCx), we encountered a coronary perforation classified as Ellis type III while using a 2.5/20 mm NC balloon inflated to 12 atm for 12 seconds. In response, we performed stent placement from the proximal LCx to OM2 using the Xience Xpedition drug-eluting stent (DES) measuring 2.5/28 mm. Subsequently, we conducted extended balloon inflation (intermittent) for five minutes. Despite these efforts, the coronary perforation, still classified as Ellis type III, persisted. We decided to employ intrastent stenting (a second DES strategy) with the Coroflex Isar DES measuring 2.5/28 mm, followed by prolonged balloon inflation. The outcome revealed no remaining perforation, Thrombolysis in Myocardial Infarction (TIMI) III flow, and no complications such as pericardial effusion after 48 hours of monitoring. The implantation of a second DES proved to be a practical approach for managing a significant CAP.